The Types of Popular Religions in China and Their Internal Relationships (Journal for the Study of Religion and History (JSRH), 2025)
There are many types of popular religions in China, and there is an internal logical structural relationship between them. From the perspective of social cooperation and its equilibriums, folk beliefs originate from specific social cooperation ethics or functional expressions of local equilibriums, and do not deliberately construct the “overall equilibrium of social cooperation ethics”. Here, “rampant worship” (淫祀) refers to the superabundance of functional beliefs. While both the universal popular god beliefs and folk sects aim to cover all types of social cooperation ethics and clearly have construction of “overall equilibrium”, the universal popular gods have an affinity with the three mainstream religions, and the “horizontal cooperation ethics” is regarded as its superior ethics, so that it can further build “pluralistic unity” (多元一体) religious pattern with the three mainstream religions; at the same time folk religious sects are institutional religions that are heterogeneous to mainstream religions and have been subjected to continuous and severe official suppression.